BACA TULIS ALQURAN BAGI TENAGA CLEANING SERVICE RUMAH SAKIT LAMADDUKELLENG DI KAB. WAJO SULAWESI SELATAN - Badaruddin Kaddas (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
The health of the human body is in the most vital position. A clean and healthy hospital environment will make your body feel comfortable and well maintained. Cleaning service is one of the elements that determines the cleanliness of the hospital environment. Cleaning service at Wajo Lamaddukelleng Hospital is considered to have high performance in carrying out its duties to realize a clean and healthy hospital environment. According to the cleaning service experience in carrying out their duties is not enough with educational capital related to environmental health and cleanliness but also requires religious knowledge including the ability to read and write the Koran as a living capital for them. One of the efforts made to find out whether cleaning service personnel are able to read and write the Koran is carried out a study. The results showed that there were still many who were unable to read and write the Quran so that they needed assistance in the form of Qur'anic reading and writing training for cleaning the servise of the Wajo Lamaddukelleng Hospital. This has an indirect impact on carrying out their duties in realizing health for all.